The prevalence of overweight, obesity and central obesity in six regions of Croatia : results from the Croatian adult health survey - Fišter, Kristina (Array, 2009)
Summary: Our aim was to estimate the prevalence of overweight, obesity and increased waist circumference in the adult population of Croatia and investigate regional differences in six regions of Croatia. Using the data from the 2003 Croatian Adult Health Survey we estimated the overall prevalence of overweight, obesity and increased waist circumference for the entire population of Croatia at 38.11%, 20.34% and 43.52%, respectively. For men, this was 43.2%, 20.1% and 34.98% and for women 33.6%, 20.6% and 51.13%, respectively for the three indicators of increased body weight. We found conflicting evidence as to whether the Mediterranean part of the country, compared with the continental part, bears a lesser degree of cardiovascular risk. Planners should pay particular attention to the Northern region, where the burden of increased body weight was the highest